Odpowiedzi

2009-11-19T14:37:30+01:00
X² + y² -2x +4y -5 = 0
(x -1)² - 1 +(y +2)² -4 - 5 = 0
(x -1)² + (y +2)² = 10
S = (1; -2) - środek tego okręgu
O = (0;0) - początek układu współrzędnych
y = ax + b
-2 =a + b
0 = b
-----------------
a = -2 oraz b =0
Czyli
y = -2x
2009-11-19T14:58:39+01:00
X² + y² -2x +4y -5 = 0
(x -1)² - 1 +(y +2)² -4 - 5 = 0
(x -1)² + (y +2)² = 10
S = (1; -2) - środek tego okręgu
O = (0;0) - początek układu współrzędnych
y = ax + b
-2 =a + b
0 = b
-----------------
a = -2 oraz b =0
Czyli
y = -2x